Schlachtfelder : Alltägliches Wirtschaften in der nationalsozialistischen Agrargesellschaft 1938–1945 - Langthaler, Ernst 1965- (Böhlau, 2016)
Taking the province of Niederdonau as an example, this pioneer study highlights everyday fields-of-force between National Socialism and agrarian society in which rural actors competed for resources among themselves and with official functionaries. The megaproject of ‘volkish productivism’ – the creation of an efficient peasantry in ‘racial’ and economic terms – got stuck with regard to technical development. However, with regard to institutional development, there emerged a pathway towards an alternative modernity beyond Liberalism and Communism